Economic Policies and Microeconomic Stability A Literature Review and Some Empirics - Garda, Paula (OECD Publishing, 2014)
The decline in macroeconomic volatility from the 1980s to the onset of the Great Recession did not, in general, translate into more microeconomic stability. While microeconomic volatility can reflect growth-generating processes, such as creative destruction and re-allocation of resources, consumption growth volatility weighs on households' welfare. This study reviews the existing literature on the link between economic policies and economic stability at the firm and household level. Based on firm-level and household-level data for a wide range of OECD countries, it also provides preliminary results on sources and patterns of microeconomic volatility
Keywords: Economics